2002
DOI: 10.2214/ajr.178.6.1781403
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging—Detected Breast Lesions: Histopathologic Correlation of Lesion Characteristics and Signal Intensity Data

Abstract: The classification of exclusively MR imaging-detectable breast lesions according to a combination of morphologic and perfusion parameters including the late enhancement pattern helps identify the lesions for which interventional MR imaging is required. Quantitative signal intensity data alone do not suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 31 publications
1
28
0
4
Order By: Relevance
“…A malignant tumour may well enhance with type I and type II shapes but heterogeneous nature of enhancement and variety of curve shapes in different anatomical areas is strongly suggestive of malignancy [8,16], reflecting a polymorphous cell population and tumour necrosis. Therefore a heterogeneous lesion must be ROI-averaged in order to gather information that is representative of the whole lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A malignant tumour may well enhance with type I and type II shapes but heterogeneous nature of enhancement and variety of curve shapes in different anatomical areas is strongly suggestive of malignancy [8,16], reflecting a polymorphous cell population and tumour necrosis. Therefore a heterogeneous lesion must be ROI-averaged in order to gather information that is representative of the whole lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The vascularisation of the malignant lesions resulting from neo-vessels, that are the basis of exponential tumour growth, is one of the major reasons that dynamic features of MRI have played a crucial role in breast cancer for a decade [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first to apply Gd -DTPA as a contrast agent in breast MRI was Heywang et al in 1985. Following that in 1989 Kaiser et al first reported dynamic breast MRI, as a modality designed to track rapid changes in signal intensity (7,14,24). Changes in the post-contrast signal intensity helped to distinguish lesions according to characteristic enhanced accumulation of contrast agent could then be related to higher tissue microvascularity (1,7,12,13,15,17,18).…”
Section: Dynamic Contrast Enhanced Mri (Dce Mri)mentioning
confidence: 99%
“…Whereas it is still not standardized the method for generating kinetic curves is accepted as both inter-and intraobserver variability (7,8,10,11,20,21). In general, though, DCE MRI has excellent sensitivity despite its variable specificity for breast cancer detection (10,14,15,22,24).…”
Section: Dynamic Contrast Enhanced Mri (Dce Mri)mentioning
confidence: 99%